Estimating lake-water evaporation from data of large-aperture scintillometer in the Badain Jaran Desert, China, with two comparable methods - P.-F. Han; X.-S. Wang; X. Jin; B. X. Hu (Proceedings of the International Association of Hydrological Sciences, 2018)
Accurate quantification of evaporation (E0) from open water is vital in arid regions for water resource management and planning, especially for lakes in the desert. The scintillometers are increasingly recognized by researchers for their ability to determine sensible (H) and latent heat fluxes (LE) accurately over distances of hundreds of meters to several kilometers, though scintillometers are mainly used to monitor the land surface processes. In this paper, it is installed on both sides of the shore over a lake. Compared to the data of evaporationpan, the scintillometer was successfully applied to Sumu Barun Jaran in Badain Jaran Desert using the classical method and the proposed linearized β method. Due to the difficulty in measuring water surface temperature and the easiness to monitor the water temperature at different depths, it is worth thinking that if is feasible to utilize the shallow water temperature instead of the water surface temperature and how much errors it will cause. Water temperature at 10 and 20 cm depths were used to replace the lakewater surface temperature in the two methods to analyze the changes of sensible and latent heat fluxes in hot and cold seasons at halfhour time scales. Based on the classical method, the values of H were almost barely affected, and the average value of LE using water temperature at 20 cm depth is 0.8–9.5 % smaller than that at 10 cm depth in cold seasons. In hot seasons, compared to the results at 10 cm depth, the average value of H increased by 20–30 %, and LE decreased by about 20 % at 20 cm depth. In the proposed linearized β method of scintillometer, only the slope of the saturation pressure curve (Δ) is related to the water surface temperature, which was estimated using available equations of saturated vapor pressure versus temperature of the air. Compared to the values of estimated by the air temperature, while the water surface temperature are replaced by water temperature at 10 and 20 cm depths, in different seasons, the errors of 2–25 % in Δ were caused. Thus was calculated by the original equation in the proposed linearized β method of scintillometer. Interestingly, the water temperature at 10 and 20 cm depths had little effect on H, LE (E0) in different seasons. The reason is that the drying power of the air (EA) accounted for about 85 % of the evaporation (i.e. the changes of Δ have only about 3 % impact on evaporation), which indicated that the driving force from unsaturated to saturated vapor pressure at 2 m height (i.e. the aerodynamic portion) has the main role on evaporation. Therefore, the proposed linearized β method of scintillometer is recommended to quantify the H, LE (E0) over open water, especially when the water surface temperature cannot be accurately measured.